2012
DOI: 10.1111/j.1365-2966.2012.20789.x
|View full text |Cite
|
Sign up to set email alerts
|

Rossby wave instability in 3D discs

Abstract: The Rossby wave instability (RWI) is a promising mechanism for producing large‐scale vortices in protoplanetary discs. The instability operates around a density bump in the disc, and the resulting vortices may facilitate planetesimal formation and angular momentum transfer in the disc dead zone. Most previous works on the RWI deal with 2D (height‐integrated) discs. However, vortices in 3D may have different dynamical behaviours from those in 2D. Recent numerical simulations of the RWI in 3D global discs by Meh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 48 publications
8
63
2
Order By: Relevance
“…Recently published studies (Lin 2012;Meheut et al 2012) indicate and confirm that the Rossby wave instability both endures in three-dimensional settings and appears to be dominated by the (largely) two-dimensional dynamical process originally characterizing the effect. A reduced shallow-water system that is nonasymptotic will aid in better understanding the development of this instability as well as others that may be concurrently present in these flow configurations.…”
Section: Summary and Discussionmentioning
confidence: 87%
“…Recently published studies (Lin 2012;Meheut et al 2012) indicate and confirm that the Rossby wave instability both endures in three-dimensional settings and appears to be dominated by the (largely) two-dimensional dynamical process originally characterizing the effect. A reduced shallow-water system that is nonasymptotic will aid in better understanding the development of this instability as well as others that may be concurrently present in these flow configurations.…”
Section: Summary and Discussionmentioning
confidence: 87%
“…One intriguing characteristic of these vortices is that the vertical displacements of gas in the vortices centres over the whole vertical scale height of the disk. This was first obtained in numerical simulations (Meheut et al 2010) and then confirmed analytically (Meheut et al 2012b;Lin 2012). These structures are of particular interest for the study of the dust concentration.…”
Section: Introductionmentioning
confidence: 98%
“…We used the Lax-Friedrich scheme (see Tóth 1996) with a Koren limiter (Koren 1993). A global simulation of the disk is needed to fully capture the RWI, but as the instability is symmetric about the midplane of the disk we only need to compute the upper half of it (Meheut et al 2010(Meheut et al , 2012b. For those reasons, the disk is simulated on a cylindrical grid with r [1, 6 AU], ϕ [0, 2π], and z [0, 0.5 AU].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical structure of the modes has recently be studied in more detail (Meheut et al 2012;Lin 2012) with dedicated tools as those presented in Zhang & Lai (2006).…”
Section: Outlooksmentioning
confidence: 99%